Renal concentrating capacity is linked to blood pressure in children with autosomal dominant polycystic kidney disease - Seeman, T; Dusek, J; Vondrák, K; Bláhová, K; Simková, E; Kreisinger, J; Dvorák, P; Kyncl, M; Hríbal, Z; Janda, J (Physiological research, 2004)
Impaired glomerular filtration rate (GFR) is a risk factor for the development of hypertension in patients with autosomal dominant polycystic kidney disease (ADPKD). However, markers of tubular function were not tested whether they are linked to hypertension or blood pressure (BP) level. The aim of our study was to investigate the relationship between renal concentrating capacity and BP in children with ADPKD. Fifty-three children (mean age 11.8+/-4.4 years) were investigated. Standardized renal concentrating capacity test was performed after nasal drop application of desmopressin, BP was measured by ambulatory BP monitoring (ABPM). Renal concentrating capacity was decreased in 58 % of children. The prevalence of hypertension was significantly higher in children with decreased renal concentrating capacity (35 %) than in children with normal renal concentrating capacity (5 %) (p<0.05). Significant negative correlations were found between renal concentrating capacity, ambulatory BP and number of renal cysts (r = -0.29 to -0.39, p<0.05 to p<0.01). In conclusion, the concentrating capacity is decreased in about half of the patients and is linked to BP. Decreased renal concentrating capacity should be considered.
Keywords: Humans; Polycystic Kidney, Autosomal Dominant; Kidney Concentrating Ability; Risk Factors; dítě; polycystické ledviny autozomálně dominantní; Child; Female; rizikové faktory; dospělí; lidé; renální hypertenze; koncentrační schopnost ledvin; předškolní dítě; Adult; ženské pohlaví; krevní tlak; Hypertension, Renal; Male; Adolescent; Statistics as Topic; vyšetření funkce ledvin; Risk Assessment; mužské pohlaví; statistika jako téma; Blood Pressure; Child, Preschool; hodnocení rizik; mladiství; Kidney Function Tests